Exploring Of English Language Teachers' Practice Of Using Supplementary Materials In Tefl Classes - Mulugeta Akele (My University, 2017)
The purpose of this study was to investigate English language teachers' practice of using supplementary materials, to assess how the perceptions' of teachers and students influence their language competency, and to identify the extent to which the teachers use supplementary materials. To conduct the study, quantitative survey method was employed. The study was conducted in six selected secondary schools of Arada Sub-City in Addis Ababa City Government Administration, and the data were collected from 50 students,37 English language teachers and 6 pedagogical center officers' and 6 librarians' documents of the past three years(2015-2017) of the six secondary schools of the sub city. In the selection of the sample population purposive and systematic sampling were used. The main instruments of data collection were questionnaires, document analysis, and classroom observation checklist. The data were analyzed using percentage, mean and grand mean. The findings of the study revealed that the main implementers of using supplementary materials and teaching aids (teachers) have perceived using supplementary materials positively but in practical, it was opposite. Which means the result showed that teachers did not use adequately supplementary materials. Similarly, their perception was positive for using Supplementary Materials in the actual classroom teaching-learning process but in practice, their usage was very low. Among the factors affecting the effective implementation of using supplementary materials; Teachers and Students' tendency to traditional teaching method, lack of teachers' interest and lack of instructional materials were the major ones. Finally, recommendations were forwarded based on the major findings so, as to minimize problems encountered and maximize the implementation of using supplementary materials and teaching aids.